2016
DOI: 10.1093/bja/aew188
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative assessment of regional ventilation during changing body positions and ventilation conditions by electrical impedance tomography

Abstract: Electrical impedance tomography was able to identify and quantify on a breath-by-breath basis circumscribed areas, so-called silent spaces, within healthy lungs that received little or no ventilation during general anaesthesia, capnoperitoneum, and different body positions. As these silent spaces are suggestive of atelectasis on the one hand and overdistension on the other, they might become useful to guide individualized protective ventilation strategies to mitigate the side-effects of anaesthesia and surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 23 publications
3
69
0
Order By: Relevance
“…Considering that EIT in its current form has not yet been adopted in clinical routine, we are convinced that enhancing EIT-images (e.g., by adding anatomical information extracted from CT scans) has the potential to facilitate the interpretation of EIT-images, and might allow the computation of novel and clinically meaningful parameters (e.g., Silent Spaces [ 33 ]). Still, EIT-image reconstruction remains a challenge, due to the ill-posed nature of EIT and the lack of clinical standards.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that EIT in its current form has not yet been adopted in clinical routine, we are convinced that enhancing EIT-images (e.g., by adding anatomical information extracted from CT scans) has the potential to facilitate the interpretation of EIT-images, and might allow the computation of novel and clinically meaningful parameters (e.g., Silent Spaces [ 33 ]). Still, EIT-image reconstruction remains a challenge, due to the ill-posed nature of EIT and the lack of clinical standards.…”
Section: Discussionmentioning
confidence: 99%
“…EIT data were continuously recorded and analyzed offline. The following EIT-derived parameters were measured: Dependent and nondependent “silent spaces,” as previously described [ 22 ]: For each breath, pixels within the ROI showing impedance changes < 10% of the maximal impedance change were determined. The silent spaces were categorized into dependent silent spaces (DSSs) and nondependent silent spaces (NSSs) by a virtual line perpendicular to the gravity vector passing through the center of ventilation (CoV; see details see below ).…”
Section: Methodsmentioning
confidence: 99%
“…EIT can identify and quantify breath-by-breath poorly ventilated lung units, also called silent spaces . In a recent study, researchers suggested that in postoperative patients with healthy lungs, silent spaces in the dependent lungs may indicate atelectasis, whereas increase in silent spaces in the nondependent lungs may correspond to overdistention [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, only signals from the CT-defined lung regions were analyzed (Figs. 1 and 2 ) [ 38 ]. EIT images were low-pass filtered to suppress cardiac-related impedance changes.…”
Section: Methodsmentioning
confidence: 99%